Psychological factors associated with Chinese international students’ well-being in the United States: A systematic review - Yin, Zizhuo; Ong, Lee Za; Qiao, Ming (Journal of International Students, 2024)
Chinese international students’ well-being is an important part to notice with the rapid number of Chinese international students in the U.S and the increasing number of depressions in college. This article systematically reviews support for the diverse psychological factors related to Chinese international students in the U.S. with mental health problems. A systematic review of articles using analytical method were conducted followed PRISMA guideline. 1600 studies were initially reviewed from EBSCO, ProQuest, etc. After examining inclusive and exclusive criteria, 30 studies were included in the full review.19 psychological factors associated with Chinese international students’ well-being were found and the positive or negative relationships between the factors were presented. Result showed social support is positively associated with CIS’s well-being and is correlated with acculturative adjustment for improving psychological well-being. This research revealed the importance of considering culture psychology in mental health professions, such as acculturation, language issues, and social support.